Coal gasification-combustion system − Part I: Principle and nitrogen migration characteristics - Yang, Shaobo; Ren, Qiangqiang; Han, Shaobo; Cui, Ruifang; Hu, Yujie; Heng, Yuqian; Dong, Shilong; Li, Linxuan; Gong, Mengyin; Liang, Chen; Guo, Shuai; Fang, Neng; et al. (Fuel (Guildford), 2025)
•A coal high temperature gasification-combustion technology is proposed.•The coal high temperature gasification-combustion theory is expounded.•The experimental verification of 200 kW coal gasification-combustion is conducted.•90.7% of coal-N is reduced to N2 during the gasification process of coal.•The flameless and efficient combustion of gasification fuel is realized. In response to the requirements of new power systems and the need for clean and efficient coal utilization, a coal gasification-combustion technology has been proposed. By constructing a coal high temperature gasification reaction system, coal’s complex components are separated through high-temperature gasification, allowing for the directional conversion and removal of nitrogen and inorganic components. This completes the “purification” process of coal, converting it into a clean carbon fuel primarily based on CO and H2. A 200 kW coal gasification-combustion experiment was conducted to test the effects of high-temperature gasification. The carbon conversion rate reached 76.9 %, the removal rate of inorganic components was 70.0 %. This high-temperature and strongly reducing environment in the coal gasification process facilitates coal nitrogen precipitation and reduction, with 93.4 % of coal nitrogen precipitating into the gas phase, 90.7 % of which is converted into N2. The coal gasification process promotes the conversion of effective active components in coal into syngas, enhances the reactivity of char, and strengthens the deep reduction and directional conversion of coal nitrogen. The gasification char nitrogen and NH3 in hot fuel are the primary sources of NOx formation during subsequent combustion processes. The gasification hot fuel, mainly composed of CO, H2, and small amount of active coke, achieves mild and efficient flameless combustion through an organized combustion process. The combustion efficiency reaches 99.7 %, and the NOx emission is 47.6 mg/m3 (@ 6 % O2), only 1.62 % of coal nitrogen is finally converted into NOx. This gasification-combustion technology realizes high-efficiency and ultra-low nitrogen coal combustion. Based on the above results, Part II will further elaborate on the regulation of the high-temperature gasification process and the mild combustion process, aiming to achieve lower NOx emission and higher combustion efficiency.